2001
DOI: 10.1002/bit.1150
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) composition in recombinant Salmonella enterica serovar typhimurium

Abstract: A recombinant strain of Salmonella enterica serovar Typhimurium (mutant in propionate-activation activity) was metabolically engineered to control the composition of poly(3-hydroxybutyrate-co-3-hydroxy- valerate) (PHBV), a polyhydroxyalkanoate copolymer with commercially desirable properties. A gene (prpE) encoding propionyl-CoA synthetase was placed under the control of the IPTG-inducible taclacUV5 promoter (P(taclacUV5)) while the polyhydroxyalkanoate synthesis operon (phaBCA) from Acinetobacter sp. RA3849 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 52 publications
2
41
1
2
Order By: Relevance
“…PHA synthesis experiments were performed in morpholinopropanesulfonate (MOPS)-buffered medium (40) with 274 mM glycerol under aerobic conditions by using the method described previously (1). Propionic acid (8 mM) was added in experiments involving exogenous propionate but was omitted in experiments involving pMMB-pha and pBAD-Cro, which tested the propionate-independent pathway for HV accumulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PHA synthesis experiments were performed in morpholinopropanesulfonate (MOPS)-buffered medium (40) with 274 mM glycerol under aerobic conditions by using the method described previously (1). Propionic acid (8 mM) was added in experiments involving exogenous propionate but was omitted in experiments involving pMMB-pha and pBAD-Cro, which tested the propionate-independent pathway for HV accumulation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a well-characterized S. enterica prpC mutant (62) was chosen as the host strain for this study. Like E. coli, S. enterica does not naturally accumulate PHA, and it has a number of advantages as a recombinant PHBV producer (1,31). Furthermore, preliminary results indicated that S. enterica is a better host for reconstituting Sbm and YgfG activities than E. coli.…”
mentioning
confidence: 99%
“…Two samples were subjected to acid extraction before they were fixed and examined by electron microscopy (F and G). Bars ϭ 1 M. (4,6,20) because then the nitrogen for CGP would also be missing. The only conditions under which significantly larger amounts of CGP were accumulated was addition of arginine as a carbon source at relatively high concentrations (75 mM).…”
Section: Fig 3 Microscopic Inspection Of Cells Of a Calcoaceticusmentioning
confidence: 99%
“…1). One leads to the formation of a C 4 monomer (3-hydroxybutyrate) in the copolymer, and the other leads to the formation of a C 5 monomer (3-hydroxyvalerate) (1,36). The C 5 monomer is formed through the condensation of acetyl-coenzyme A (acetyl-CoA) and propionyl-CoA by the action of ␤-ketothiolase.…”
mentioning
confidence: 99%
“…In addition, many bacteria showed poor 3HV yields from substrate propionate (Y 3HV/Prop ) (32). The overexpression of propionyl-CoA synthetase (encoded by prpE) in recombinant Salmonella enterica or Escherichia coli improved the 3HV fraction in the copolymer up to 25 mol% (1,40). Besides the uptake limitation of propionate, the endogenous catabolism of propionyl-CoA is also a limiting factor for producing PHBV with a high 3HV fraction.…”
mentioning
confidence: 99%